Diurnal changes of retinal microvascular circulation and RNFL thickness measured by optical coherence tomography angiography in patients with obstructive sleep apnea–hypopnea - Cai, Yi; Liu, Wen-Bo; Zhou, Miao; Jin, Yu-Tong; Sun, Guo-Sheng; Zhao, Long; Han, Fang; Qu, Jin-Feng; Shi, Xuan; Zhao, Ming-Wei (Frontiers in Endocrinology, 2022)
Purpose: To evaluate capillaries perfusion and retinal nerve fiber layer (RNFL) thickness diurnal changes in macular/optic disc regions in subjects with or without obstructive sleep apnea-hypopnea (OSA) by using spectral-domain optical coherence tomography angiography (OCTA). Methods: This study enrolled 14 participants with mild-to-moderate OSA, 12 participants with severe OSA, and 9 healthy individuals. Every subject filled out the Berlin questionnaire and received comprehensive ocular examinations at 20:00 and 6:30 just after the polysomnography examination respectively. The systemic and ocular clinical characteristics were collected, and OCTA scans were performed repeatedly. Blood flow and RNFL thickness parameters were exported using built-in software and analyzed accordingly. Results: After sleep, the RPC vessel density at the inside-disc region decreased significantly in the mild-to-moderate group (p=0.023). RNFL changes before and after sleep in the inferior-nasal and peripapillary region were significantly different (p=0.003; p=0.043) among the three groups, and Post hoc tests verified the significant difference in diurnal changes between the mild-to-moderate group and the control group in pairwise comparisons (p=0.006; p=0.02). Other vessel density (VD) variables, including macular and choriocapillaris are relatively comparative and stable. Conclusions: Blood flow and RNFL thickness overnight change around optic disc areas might emerge in OSA patients. Although there may be physiological fluctuations, aberrant diurnal changes may signal a decrease in micro-environmental stability associated with the development of various ocular diseases such as glaucoma. Other VD variables, especially macular VDs are relatively stable in eyes of patients with OSA with different severity.